Crest factor minimization: A neural network approach - Mastorakis, Nikos E. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a state-space model is proposed for the minimization problem of the crest factor in the case of a multi sine signal. This state-space model provides a stable neural network and it can be studied using computer simulation.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka